Beverage Cans Crusher Machine Patents: A Review (Part IV) - Elfasakhany, Ashra (Asian Review of Mechanical Engineering, 2019)
While I worked in my invention for can crusher machine (patent No. 4610 in 2016), I studied all the early patents for such machines all over the world, which is hard task. This paper aims at summarizing the early patents for can crusher machines within the period from 1994 to 1995, e.g., couple of years. We presented here a title of each patent, patent number, name of the inventor, the patent issued date and an overview of patent layout. This study is thought to be very useful for inventors who worked on patents for next generation of can crusher machines.